Pengembangan Sistem Informasi Manajemen Keuangan Peternakan Kambing (Studi Kasus: Yoga's Farm Kabupaten Tulungagung) - Rizki Indra Fanani; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The need for information at this time is very important in various aspects of life. Yoga's Farm is a farm that runs the process of fattening goats, selling goats, selling cattle medicine, and selling various types of animal feed. This farm has enough benefits but all financial reporting is still not neatly arranged. Financial reporting is only done manually, this results in many finances that are not defined as useful. From the problems that arise, an information system is developed that will facilitate the processing of financial data. Financial reporting systems can also be printed and display the benefits of goat farming. The method used in development is waterfall. Whereas the framework used in developing this information system is Laravel. Testing for functional systems is a validation test, the results of validation testing state that the system is 100% valid, indicating that it is functioning properly and in accordance with user expectations. Testing for nonfunctional requirements is testing browser compatibility, the results suggest that the system can run on 9 different browsers. However, in IE (Internet Explorer) version 11 there are critical issues, 9 major issues from 16 browser versions and 5 minor issues from 10 browser versions.